One-Click CT-Based Pipeline for Regional Quantification of Aortic Valve Fibrocalcific Degeneration - Marta Liberotti; Anna Palmisano; Alberto Colombo; Davide Vignale; Federica Piccione; Marco Bruno Ancona; Matteo Montorfano; Antonio Esposito (Annals of Biomedical Engineering, 2026)

Underexploited Caatinga fruits as drivers of chemical and sensory aspects, and microbial communities in ginger beers - Louise Iara Gomes de Oliveira; Viviane Maria de Sousa Fontes; Whyara Karoline Almeida da Costa; Bruno Silva Dantas; Débora Pinhatari Ferreira; Arão Cardoso Viana; Victoria Mesa; Marcos dos Santos Lima; Tatiana Colombo Pimentel; Marciane Magnani (Food Bioscience, 2026)

The italian national genomic strategy: current status, challenges, and future perspectives in clinical practice and public health - Francesco Andrea Causio; Sara Farina; Alessandra Maio; Flavia Beccia; Luigi Russo; Valentina Baccolini; Matteo Chiara; Americo Cicchetti; Gualtiero I. Colombo; Giovanni Comandé; Domenico Coviello; Ruggero De Maria; et al. (Journal of Community Genetics, 2025)
This article presents the outcomes of a national initiative aimed at developing a technical document to support the future Italian National Genomic Strategy, carried out from 2021 to 2024 through the collaboration of 14 research institutions. The project was designed to align with major European genomic initiatives, particularly the “1 + Million Genomes” (1 + MG) Declaration and its supporting programs, including Beyond 1 Million Genomes (B1 + MG), the Genomic Data Infrastructure (GDI), and Genome of Europe (GoE). The initiative was structured around 12 National Mirror Groups (NMGs), each addressing a specific domain such as clinical implementation, ethical and legal issues, data governance, health economics, and public engagement. Through expert consensus and coordinated activities, the project produced a comprehensive technical document outlining seven strategic lines and related intervention areas. These include the integration of genomic testing into clinical practice, development of specialized genomic centers, creation of a national genomic data infrastructure, professional training, and public education. The proposed strategy emphasizes equitable access to genomic medicine, the use of health technology assessment to evaluate new technologies, and the importance of citizen engagement and literacy. By fostering collaboration among institutions, healthcare professionals, and the public, the final goal is to position Italy as a leader in genomic medicine and ensure the responsible, effective, and ethical use of genomics in public health and clinical care.

Dietary differences in males and females of a strongly sexually dimorphic ungulate - Alice Brambilla; Xavier Bal; Maria Letizia Lusetti; Mattia Colombo; Andrea Mainetti; Lukas Keller; Bruno Bassano (European Journal of Wildlife Research, 2024)
Detailed knowledge of dietary preferences in wild species are important both for understanding evolutionary processes as well as for their conservation. By means of DNA metabarcoding analysis of faecal samples, we investigated the diet of Alpine ibex ( Capra ibex ), a mountain ungulate characterised by strong sexual dimorphism and segregation, and analysed differences between male and female diet. Despite a low level of selectivity, we found differences in the diet of males and females that consumed different plant in different quantities. Differences were maintained during both spring and summer. Males tended to feed more on plants richer in fibres (i.e., grasses and sedges) and showed stronger seasonal differences while females consumed more digestible plant families (i.e., forbs). Differences in diet between male and female Alpine ibex are compatible with the strong sexual dimorphism and segregation typical of the species and with female reproductive constraints. These results also show that conservation actions have to take into account different ecological needs of males and females in species characterized by sexual dimorphism and segregation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

New Mutations in NEB Gene Discovered by Targeted Next-Generation Sequencing in Nemaline Myopathy Italian Patients - Daniela Piga; Francesca Magri; Dario Ronchi; Stefania Corti; Denise Cassandrini; Eugenio Mercuri; Giorgio Tasca; Enrico Bertini; Fabiana Fattori; Antonio Toscano; Sonia Messina; Isabella Moroni; et al. (Journal of Molecular Neuroscience, 2016)

Deficits in memory and visuospatial learning correlate with regional hippocampal atrophy in MS - Giulia Longoni; Maria A. Rocca; Elisabetta Pagani; Gianna C. Riccitelli; Bruno Colombo; Mariaemma Rodegher; Andrea Falini; Giancarlo Comi; Massimo Filippi (Brain Structure and Function, 2015)

Fluticasone furoate maintains epithelial homeostasis via leptin/leptin receptor pathway in nasal cells - Andreina Bruno; Stefania Gerbino; Maria Ferraro; Liboria Siena; Angela Bonura; Paolo Colombo; Stefania La Grutta; Salvatore Gallina; Antonella Ballacchino; Marco Giammanco; Mark Gjomarkaj; Elisabetta Pace (Molecular and Cellular Biochemistry, 2014)

Design, synthesis and activity evaluation of mannose-based DC-SIGN antagonists - Nataša Obermajer; Sara Sattin; Cinzia Colombo; Michela Bruno; Urban Švajger; Marko Anderluh; Anna Bernardi (Molecular Diversity, 2011)